Prevalence of vestibular and balance disorders in children and adolescents according to age: A multi-center study. (March 2017) - Lee, Jong Dae; Kim, Chang-Hee; Hong, Seok Min; Kim, Sung Huhn; Suh, Myung-Whan; Kim, Min-Beom; Shim, Dae Bo; Chu, Hosuk; Lee, No Hee; Kim, Minbum; Hong, Sung Kwang; Seo, Jae-Hyun
Abstract: Objectives: Children differ from adults in the expression of dizziness symptoms and the causes of dizziness. In several studies, benign paroxysmal vertigo of childhood (BPVC) and vestibular migraine (VM) were seen exclusively in children with vertigo, but the age threshold used to define 'children' varies, and there are few reported studies about adolescents with dizziness. In this study, we investigated the prevalence of vestibular and balance disorders according to age category in a multi-center study (otolaryngology departments of 11 hospitals) of children and adolescents. Methods: Children and adolescents aged under 18 who visited the otolaryngology departments of 11 hospitals for dizziness were included. We classified the patients into three categories: preschool (up to and including 6-year-olds), school age (7- to 12-year-olds), and adolescents (13- to 18-year-olds). These patients were reviewed retrospectively based on their clinical charts. Results: In the preschool age group, BPVC was most common, followed by VM. In the school-age group, BPVC and VMs were most common, followed by psychogenic vertigo and benign paroxysmal positional vertigo (BPPV). In adolescents, VM was the most common, and Ménière's disease, cardiogenic vertigo, and BPVC, which are seen primarily in adults, were also seen in some adolescents. Conclusion: In children and adolescents with dizziness, VM and BPVC were the most common diseases, and prevalence of disease by age showed differing distributions. These findings will help in diagnosing and managing children and adolescents with vertigo.